Reply to Dumke, C. Comment on "Fan et al. Efficacy of Ingesting an Oral Rehydration Solution after Exercise on Fluid Balance and Endurance Performance. Nutrients 2020, 12, 3826" Reply - Lee, Jason Kai Wei (MDPI, 2021)
10.3390/nu13093215